Some International Law Aspects of Safety of Civil Aircraft Flying over the Areas of Armed Conflicts and Military Exercises - A. A. Batalov (Московский журнал международного права, 2018)
Introduction. Despite the international aviation community’s attempts aimed at improvement of safety of air transport and reduction of the number of air accidents, unfortunately, many threats to safety of civil aircraft still exist to date, including armed conflicts and other military activities taking place in different parts of our planet. Malaysian Boeing 777-200 crash of 17 July 2014 in the eastern Ukraine killing 283 passengers and 15 crew members has become the tragedy clearly showing the risks, to which the civil aircraft and passengers on board flying in the airspace over the areas of armed conflicts, are exposed. In light of this accident, the author examines the present international legal regime of safety of civil aircraft flying over the areas of armed conflicts and military exercises, identifies the problems of this regime and proposes the ways of its improvement.Materials and methods. The present research has been conducted on the basis of international air law treaties, the documents of International Civil Aviation Organization (ICAO), as well as the works of Russian and foreign international law experts. The methodology of the research is based upon general scientific and special methods, including dialectical method, methods of analysis and synthesis, deduction and induction, comparative legal method.Research results. On the basis of his research the author concludes that neither the present-day international legal regime of safety of civil aircraft flying over the areas of armed conflicts and military exercises, nor existing rules of international air law prohibiting use of weapons against civil aircraft can prevent accidents similar to Malaysian airplane crash of 17 July 2014. In view of this conclusion, the author proposes improvement of international legal regime of safety of civil aviation, and in particular, amendment of the Convention on International Civil Aviation of 1944 (“Chicago Convention of 1944”) aimed at enhancement of States’ obligations relating to restriction of flights of civil aircraft within their sovereign airspace during armed conflicts or other military activities.Discussion and conclusions. The author examines treaty and customary rules of international law governing the issues of safety of civil aircraft flying over the areas of armed conflicts and military exercises as well as ICAO standards and other acts (documents) and concludes that they do not precisely oblige the States to restrict or prohibit flights of civil aircraft in their sovereign airspace during armed conflicts, military exercises or other hazardous military activities. Moreover, the provisions of the Chicago Convention of 1944 and other international treaties prohibiting the use of weapons against civil aircraft are imperfect and do not fully protect civil aviation from different types of weapons. Therefore, the ICAO’s work following Malaysian airplane crash of 17 July 2014 for the purpose of enhancement of protection of civil aviation from the threats arising from armed conflicts and other hazardous military activities appears insufficient and must include more efficient measures, such as adoption of new international treaty rules containing precise States’ obligations.